Influence of phosphorus application on seed yield, quality and phosphorus uptake pattern of Indian mustard (Brassica juncea) cultivars: INFLUENCE OF P APPLICATION ON YIELD, QUALITY AND P UPTAKE PATTERN OF INDIAN MUSTARD - HARIDARSHAN CHOUKSEY; VIRENDER SARDANA; PUSHP SHARMA (Journal of Oilseeds Research, 2016)
A field experiment was conducted during rabi 2012-13 at the Punjab Agricultural University, Ludhiana on low P soil to study the response of Indian mustard [Brassica juncea (L.) Czern and Coss] cultivars to applied phosphorus. Application of phosphorus up to 15 kg/ha of P2O5 significantly increased the concentration and uptake of P in plants at all the growth stages, in seed and stover at harvest, and seed yield, oil content, oil yield and protein yield whereas similar increase with application of 30 over 15 kg/ha of P2O5 was significant for P concentration in seed and stover, P uptake at 90 and 120 DAS, stover and total P uptake (seed+ stover) and oil content. Seed yield (1766 kg/ha), oil yield (625 kg/ha) and protein yield (291 kg/ha) produced with application of 30 kg/ha of P2O5 was 9.9, 11.2 and 8.9 per cent, respectivelymore than that produced without application of phosphorus. Among cultivars, NRCHB 601 has significantly out performed all other cultivars for P concentration and uptake, seed-, oil- and protein-yield. Total P uptake at maturity by NRCHB 601 (21.52 kg/ha) was significantly more (18.8-54.8%) than rest of the cultivars. Cultivar NRCDR 2 contained significantly higher oil content (40.2%) than rest of the test cultivars, but, its oil yield was significantly lower than that of NRCHB 601.